2001
DOI: 10.1016/s0213-9111(01)71611-1
|View full text |Cite
|
Sign up to set email alerts
|

Validación del peso y la talla autodeclarados en población adolescente

Abstract: Analysis of BMI as a continuous variable, based on self-reported weight and height measurement data, entails a small margin of error. However, its use as a categorical variable involves a considerable underestimate of the prevalence of high BMI, and an smaller overestimate of the prevalence of low BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
2
6
0
10
Order By: Relevance
“…However, when the presence of false negatives is not a real problem, such as in long-term surveillance and trend studies, the use of estimated BMI based on reported measures is a less expensive alternative 19 . Specificity was higher for girls (92.7%) compared to boys (80.6%), consistent with other studies 19,20 . The capacity of estimated BMI based on reported measures to diagnose non-obese adolescents was satisfactory, since nine of ten adolescents that were not obese were correctly classified.…”
Section: Discussionsupporting
confidence: 92%
“…However, when the presence of false negatives is not a real problem, such as in long-term surveillance and trend studies, the use of estimated BMI based on reported measures is a less expensive alternative 19 . Specificity was higher for girls (92.7%) compared to boys (80.6%), consistent with other studies 19,20 . The capacity of estimated BMI based on reported measures to diagnose non-obese adolescents was satisfactory, since nine of ten adolescents that were not obese were correctly classified.…”
Section: Discussionsupporting
confidence: 92%
“…The few studies that have considered self-reports by underweight adolescents confirmed the result of this study, i.e. that underweight adolescents tend to over-report their BMI [10,14]. When measured weight status was not included in the linear regression model, body perception was a major predictor of the quality of self-reports.…”
Section: Discussionsupporting
confidence: 78%
“…First, self-reported weight and height were used to determine overweight and obesity, and as is already known, there is a problem with the validity and reliability of these data among adolescents (boys over-report their height, girls under-report their weight, with the consequent result of underestimation of overweight and obesity42). This probably happened in our study, but this would not affect the study of social inequalities, except if under-reporting were differential depending on parents' social class, something that, to our knowledge, has not been studied in Spain.…”
Section: Discussionmentioning
confidence: 99%